Immunogenicity of Intradermal Trivalent Influenza Vaccine With Topical Imiquimod: A Double Blind Randomized Controlled Trial. (21st July 2014) - Hung, Ivan F. N.; Zhang, Anna J.; To, Kelvin K. W.; Chan, Jasper F. W.; Li, Can; Zhu, Hou-Shun; Li, Patrick; Li, Clara; Chan, Tuen-Ching; Cheng, Vincent C. C.; Chan, Kwok-Hung; Yuen, Kwok-Yung
Abstract : Vaccine immunogenicity among the elderly is suboptimal. In this study, we demonstrate that pretreatment with topical imiquimod significantly expedited, augmented, and prolonged the immunogenicity of influenza vaccination. This strategy for influenza immunization should be considered in the elderly population. Abstract: Background. Imiquimod, a synthetic Toll-like receptor 7 agonist enhanced immunogenicity of influenza vaccine in a mouse model. We hypothesized that topical imiquimod before intradermal influenza vaccination (TIV) would produce similar effect in human. Methods. We performed a prospective 1-year follow-up, double-blind, randomized, controlled trial with adults with comorbidities. Participants were randomized to 1 of the following 3 vaccinations: topical 5% 250 mg imiquimod ointment followed by intradermal TIV, topical aqueous-cream followed by intradermal TIV, or topical aqueous-cream followed by intramuscular TIV. Patients and investigators were blinded to the type of topical treatment applied. Hemagglutination inhibition (HI) and microneutralization antibody titers were measured. The primary outcome was the day 7 seroconversion rate. Results. Ninety-one recruited participants completed the study. The median age was 73 years. On day 7, 27/30 (90%) patients who received imiquimod and intradermal TIV achieved seroconversion against the H1N1 strain by HI, compared with 4/30 (13.3%) who received aqueous-cream and intramuscular TIV ( P < .001), and 12/31 (38.7%) who received aqueous-cream and intradermal TIV ( P < .001). The seroconversion, seroprotection, and geometric mean titer–fold increase were met in all 3 strains in the imiquimod and intradermal TIV group 2 weeks earlier, and the better seroconversion rate was sustained from day 7 to year 1 ( P ≤ .001). The better immunogenicity was associated with fewer hospitalizations for influenza or pneumonia ( P < .05). All adverse reactions were self-limited. Conclusions. Pretreatment with topical imiquimod significantly expedited, augmented, and prolonged the immunogenicity of influenza vaccination. This strategy for influenza immunization should be considered for the elderly population.